(untitled) (Research, Society and Development, 2020)
The coriander presents great social and economic importance for Brazil, the search for less degrading practices is increasing in the agricultural environment, especially the use of alternative products to control seed-associated phytopathogens that cause damping off, responsible for high yield reduction. In this context, the present work had as objective to evaluate the effect of different essential oils on phytopathogen inhibition and on the development of coriander seeds inoculated with Alternaria. The experiment was conducted at the Universidade do Estado da Bahia in Juazeiro-BA and tested for essential oils of lemon grass, cloves and sage, on the development of phytopathogenic fungus and performance of coriander seeds cultivar Verdão. The experimental design was completely randomized in a factorial scheme, using the Tukey test at 5% for the effect of the oils and regression for the effect of the doses. It was observed that the oils and the doses had a significant effect on the analyzed variables, in which the essential oil of clove presented better result for the growth rate and inhibition of mycelial growth of the fungus in vitro. The essential oils did not potentiate the vigor of the seeds presenting mostly decreasing linear trend curve, however, there were no abnormalities in seedling development.